Increasing vertical resolution of three-dimensional atmospheric water vapor retrievals using a network of scanning compact microwave radiometers - Sahoo, Swaroop, author; Reising, Steven C., advisor; Bringi, V. N., 1949-, committee member; Krueger, David A., committee member (Colorado State University. Libraries, 2011)
The thermodynamic properties of the troposphere, in particular water vapor content and temperature, change in response to physical mechanisms, including frictional drag, evaporation, transpiration, heat transfer and flow modification due to terrain. The planetary boundary layer (PBL) is characterized by a high rate of change in its thermodynamic state on time scales of typically less than one hour. Large horizontal gradients in vertical wind speed and steep vertical gradients in water vapor and temperature in the PBL are associated with high-impact weather. Observation of these gradients in the PBL with high vertical resolution and accuracy is important for improvement of weather prediction. Satellite remote sensing in the visible, infrared and microwave provide qualitative and quantitative measurements of many atmospheric properties, including cloud cover, precipitation, liquid water content and precipitable water vapor in the upper troposphere. However, the ability to characterize the thermodynamic properties of the PBL is limited by the confounding factors of ground emission in microwave channels and of cloud cover in visible and IR channels. Ground-based microwave radiometers are routinely used to measure thermodynamic profiles. The vertical resolution of such profiles retrieved from radiometric brightness temperatures depends on the number and choice of frequency channels, the scanning strategy and the accuracy of brightness temperature measurements. In the standard technique, which uses brightness temperatures from vertically pointing radiometers, the vertical resolution of the retrieved water vapor profile is similar to or larger than the altitude at which retrievals are performed. This study focuses on the improvement of the vertical resolution of water vapor retrievals by including scanning measurements at a variety of elevation angles. Elevation angle scanning increases the path length of the atmospheric emission, thus improving the signal-to-noise ratio. This thesis also discusses Colorado State University's (CSU) participation in the European Space Agency (ESA)'s "Mitigation of Electromagnetic Transmission errors induced by Atmospheric WAter Vapor Effects" (METAWAVE) experiment conducted in the fall of 2008. CSU deployed a ground-based network of three Compact Microwave Radiometers for Humidity profiling (CMR-Hs) in Rome to measure atmospheric brightness temperatures. These measurements were used to retrieve high-resolution 3-D atmospheric water vapor and its variation with time. High-resolution information about water vapor can be crucial for the mitigation of wet tropospheric path delay variations that limit the quality of Interferometric Synthetic Aperture Radar satellite interferograms. Three-dimensional water vapor retrieval makes use of radiative transfer theory, algebraic tomographic reconstruction and Bayesian optimal estimation coupled with Kalman filtering. In addition, spatial interpolation (kriging) is used to retrieve water vapor density at unsampled locations. 3-D humidity retrievals from Rome data with vertical and horizontal resolution of 0.5 km are presented. The water vapor retrieved from CMR-H measurements is compared with MM5 Mesoscale Model output, as well as with measurements from the Medium Resolution Imaging Spectrometer (MERIS) aboard ESA's ENVISAT and the Moderate Resolution Imaging Spectroradiometer (MODIS) aboard NASA's Aqua and Terra satellites.